Environmental management accounting affects bank performance with mediators - Kim Quoc Trung Nguyen (PLoS ONE, 2025)
This study aims to estimate the effect of environmental management accounting (EMA) on Vietnamese bank performance under the mediating role of environmental costs. The research employs qualitative methods, such as expert interviews and surveys, alongside quantitative methods, such as Partial least squares Structural Equation Modeling (PLS-SEM). The findings revealed a positive correlation between EMA and knowledge management, green innovation, and environmental costs. Additionally, knowledge management and green innovation significantly positively influence environmental costs. Significantly, the study emphasizes the relationship between EMA and a bank’s performance, mediated by environmental costs. Recognizing the significance of environmental costs in the total cost structure, this study highlights their potential emergence in the provision of financial services. This study underscores the role of environmental accounting, which integrates the financial and management accounting aspects, in providing information on these costs.